Perché parlare oggi di sicurezza nella regione Adriatico-Ionica? - BORTOLETTO, NICO; MINARDI, Everardo (2015)
The paper emphasize the relevance of the Adriatic-Ionian Region in the present European scenario. It is stressed the need of specific policies, able to contrast the tendency to reduce the mobility and migration present trends by the securitization (and/or militarization) of all dynamics in the field. It’s showed that reassure could be achieved using different ways, for instance using economic models linked to the cooperation between the touristic/food industry and the industrial sector. For doing that it’s needed to re-engineering the professional community involved and the perception of the sea as a territory, bearer of its own cultures and specificity.